Allogeneic hematopoietic cell transplantation for adult patients with treatment-related acute myeloid leukemia during first remission: Comparable to de novo acute myeloid leukemia. (August 2016) - Tang, Fei-Fei; Huang, Xiao-Jun; Zhang, Xiao-Hui; Chen, Huan; Chen, Yu-Hong; Han, Wei; Chen, Yao; Wang, Feng-Rong; Wang, Yu; Wang, Jing-Zhi; Yan, Chen-Hua; Sun, Yu-Qian; et al.
Highlights: We compared adult T-AML and de novo AML after allo-HCT for the first time. All patients with T-AML in our study had a history of malignant disease. All patients received MAC and fifty-two percent patients received unmanipulated haplo-HCT. The 3-year OS, LFS, NRM and relapse of T-AML was comparable to de novo AML after allo-HCT. Abstract: Therapy-related acute myeloid leukemia (T-AML) is associated with poor prognosis after conventional therapy. Allogeneic hematopoietic cell transplantation (allo-HCT) has been proposed as a treatment for T-AML; however, data comparing outcomes of transplants for patients with de novo AML and T-AML are limited. Sixteen adult patients with T-AML during first complete remission after malignant disease received allo-HCT at the Peking University Institute of Hematology between January 1, 2006 and December 31, 2014. Eighty patients with de novo AML were selected using the case-pair method. The 3-year overall survival and leukemia-free survival for T-AML versus de novo AML patients were 66% vs. 79% ( P  = 0.14) and 64% vs. 77% ( P  = 0.13), respectively. The 3-year cumulative non-relapse mortality rates for T-AML versus de novo AML patients were 13% vs. 9% ( P  = 0.47), respectively; the relapse rates were 20% vs. 13% ( P  = 0.25), respectively. Our results suggest that the prognosis of T-AML is comparable to that of de novo AML after transplantation. Although T-AML shows poorer prognosis than de novo AML after conventional therapies, allo-HCT can markedly improve the prognosis of T-AML.